Economic effects of tourism: Analysis at the subnational level in Iceland - Lilja Berglind Rögnvaldsdóttir 1975- (2016)
This study explores the availability of regional statistical data on the tourism industry in Iceland and analyses the economic effects of tourism in the Þingeyjarsýslur region. This was done by gathering regional data from fieldwork in situ consisting of company interviews and visitor surveys in Þingeyjarsýslur during the period of 2013-2015. The method used in this study considered the principles of the Nordic Model as well as the Tourism Satellite Account: Recommended Methodological Framework 2008 and its applicability at the regional level. The report demonstrates the development of visitor numbers in the area as well as the development of regional accommodation statistics. The main economic findings are the total turnover by detailed industries directly related to tourism in the region as well as internal tourism consumption and tourism employment figures. The indirect effects measured in this study are partial and represent only the first round effects of tourism in the area based on purchases and other operating expenses of tourism companies in the region. Municipal tourism revenue sources are analysed and municipal income tax from the tourism industry is also calculated. The applicability of the internationally established frameworks of tourism economic impact analysis in the Icelandic regional context are discussed in this study where it emerges that due to the limited availability of regional tourism data in Iceland, methods such as the Input-Output model, Computable General Equilibrium model and tourism multipliers could not be applied in this study. Í þessari skýrslu eru kynntar niðurstöður rannsóknar á efnahagslegum áhrifum ferðaþjónustu í Þingeyjarsýslum. Markmið verkefnisins var að kanna svæðisbundið framboð gagna í ferðaþjónustu sem og að meta efnahagsleg áhrif atvinnugreinarinnar með hliðsjón af alþjóðlegri forskrift ferðaþjónustureikninga og hins norræna líkans um mat á áhrifum ferðaþjónustu. Niðurstöðurnar byggja á viðtölum við ferðaþjónustuaðila í Þingeyjarsýslum sem og ferðavenjukönnunum ...